Impact of crystallization firing process on the microstructure and flexural strength of zirconia-reinforced lithium silicate glass-ceramics - Riquieri, Hilton [UNESP]; Monteiro, Jaiane Bandoli [UNESP]; Viegas, Diogo Cabecinha; Campos, Tiago Moreira Bastos; de Melo, Renata Marques [UNESP]; de Siqueira Ferreira Anzaloni Saavedra, Guilherme [UNESP] (Elsevier, 2018)
Objectives: The aim of this study was to characterize the microstructure of two zirconia-reinforced lithium silicate (ZLS) glass-ceramics and evaluate their mechanical properties before and after the crystallization firing process (CFP). Methods: Field emission-scanning electron microscope (FE-SEM) and energy-dispersive X-ray spectroscopy (EDS) analyses were performed for microstructural characterization. To evaluate the pattern of crystallization and the molecular composition of ZLS glass-ceramics, was used X-ray diffraction (XRD). Vickers hardness, fracture toughness by the indentation method, and biaxial flexural strength were also measured. One hundred and forty ceramic discs were produced (diameter = 12 mm; thickness = 1.2 mm) and allocated among four groups (n = 30): Sfir, Sunf-ZLS Vita Suprinity; and Cfir and Cunf-ZLS Celtra Duo; fired and unfired, respectively. Statistical analysis was performed and Weibull failure probabilities were calculated. Results: Cfir showed the highest characteristic strength (251.25 MPa) and hardness (693.333 ± 10.85 GPa). Conversely, Sunf presented the lowest characteristic strength (106.95 MPa) and significantly lowest hardness (597.533 ± 33.97 GPa). According to Weibull analysis, Sunf had the highest structural reliability (m = 7.07), while Sfir presented the lowest (m = 5.38). The CFP was necessary to crystallize zirconia in the partially crystallized ZLS glass-ceramics. Sfir had a lower percentage of crystallized zirconia than did Cfir. Fractographic analyses showed that all failures initiated from an inherent critical defect in Sunf and from processing defects in the remaining groups. Significance: The CFP had a direct influence on the flexural strength and microstructural characteristics of both ZLS materials.
Keywords: Biaxial flexural strength; Computer-aided manufacturing; Dental ceramics; Dental materials